Correspondence of the sign change in organic magnetoresistance with the onset of bipolar charge transport - Bloom, Francisco L.; Wagemans, Wiebe; Kemerink, Martijn; Koopmans, Bert (Applied physics letters, 2008)
In this work we examine the transition between positive and negative organic magnetoresistance in poly[2-methoxy-5-(3′3′3′, 7′7′7′-dimethyloctyloxy)-ppp-phenylenevinylene] in order to understand how different regimes of charge transport affect the organic magnetoresistance effect. To characterize the charge transport in these devices we measured the current, low frequency differential capacitance, and electroluminescence efficiency as a function of voltage. These measurements show that the sign change of the magnetoresistance corresponds with a change from a unipolar diffusive transport below the built in voltage (Vbi)(Vbi)(V<mtext>bi</mtext>) to a regime of bipolar drift transport above VbiVbiV<mtext>bi</mtext>.